Reduction of metal artefacts from bilateral hip prostheses during lower extremity computed tomography angiography: an experimental phantom study - Omarah N. Abdalqader; Mohammad Hjouj; Mohammad Aljamal; Fawaz Hjouj; Mohamed Abuzaid; Mahmoud Mousa (Journal of Medical Radiation Sciences)
Abstract Introduction Image quality reduction due to metallic artefacts is a significant challenge during vascular computed tomography (CT) imaging of the lower extremities in patients with hip prostheses. This study aims to analyse various reconstruction algorithms' ability to reduce metal artefacts due to two types of hip prostheses during lower extremity CT angiography examinations. Methods A pelvis phantom was fabricated with the insertion of a tube filled with contrast media to simulate the femoral artery, and the phantom was then CT scanned with and without hip prostheses. Multimodal images were acquired using different kilovoltage peak (kVp) settings and reconstructed with different algorithms, such as filtered back projection (FBP), iterative reconstruction (iDose4), iterative model‐based reconstruction (IMR) and orthopaedic metal artefact reduction (O‐MAR). Image quality was assessed based on image noise, signal‐to‐noise ratio (SNR) and Hounsfield unit (HU) deviation. Results The IMR approach significantly improved image quality compared to iDose4 and FBP. For the vascular region, O‐MAR improves SNR by 5 ± 1, 23 ± 5 and 42 ± 9 for FBP, iDose4 and IMR respectively, and improves HU precision towards the baseline values by 49% and 83% for FBP and IMR, respectively. The noise reduction was 71% and 89% for FBP and IMR, and 57% for iDose4. O‐MAR greatly enhances SNR corrections among the most severe artefacts, with 29 ± 1 and 43 ± 4 for FBP and IMR, compared to iDose4 by 37 ± 7. Conclusion IMR combined with O‐MAR could improve the CT angiography of the lower extremities of patients with a hip prosthesis.